Effect of Azadirachta indica (Sapindales: Meliaceae) Oil on the Immune System of Spodoptera frugiperda (Lepidoptera: Noctuidae) Immatures. Issue 3 (18th June 2020) - Duarte, Jucelio P; Redaelli, Luiza R; Silva, Carlos Eugênio; Jahnke, Simone M
Abstract: The insect immune system includes several mechanisms responsible for defending against pathogens, parasites, and parasitoids. Some botanical insecticides, such as Azadirachta indica oil, cause changes in the immune system of various insect species. Spodoptera frugiperda is an important agricultural pest; thus, knowledge about the effect of neem oil on the immune system of this species can assist in its management. This study aimed to evaluate the effect of A. indica oil on the immune system of S. frugiperda . Caterpillars (2–3 mg) were placed individually in containers (50 ml) with approximately 10 g of diet, containing 125, 250, and 500 ppm of neem oil with propanone; the control group received only the propanone diet. In four experiments, the total number of hemocytes, the phagocytic activity, the activity of lysozyme-like enzymes, and phenoloxidase activity were measured in caterpillars at the end of the sixth instar. The total number of hemocytes in insects exposed to neem oil was 21% lower than in the control group. The percentage of cells that phagocyted the latex beads was similar among the caterpillars that ingested the different concentrations. The mean diameter of cell lysis halos was reduced only at concentrations of 125 and 250 ppm. Absorbance did not differ between treatments. Knowing that this oil reduces the number of circulation cells and the activity of lysozyme-like enzymes is of great importance to design control strategies, once the neem oil could be added to other biological agents for mortality reducing the chances of this insect surviving in the environment.